PERKEMBANGAN FINTECH PADA BANK SYARIAH DI INDONESIA: PERKEMBANGAN FINTECH PADA BANK SYARIAH DI INDONESIA - ali topan lubis (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2025)
This study analyzes the rapid development of Financial Technology (Fintech) in the Islamic banking landscape in Indonesia over the past five years. Along with the global digital transformation, Islamic banks are faced with significant opportunities and challenges in integrating Fintech innovations to improve efficiency, service reach, and competitiveness. Using a qualitative approach through a comprehensive literature study, this article identifies trends in Fintech adoption by Islamic banks, exploring opportunities such as increasing financial inclusion and developing innovative Islamic products, and highlighting challenges such as Islamic compliance, cybersecurity, and dynamic regulations. The findings show that Islamic banks are proactively adapting to the digital era, although ongoing strategies are needed to maximize the potential of Fintech while maintaining Islamic principles. This study contributes to the contemporary Islamic Economics literature and provides practical recommendations for industry players and regulators in developing a resilient and sustainable Islamic Fintech ecosystem.